USING TEACHER’S INDIRECT FEEDBACK STRATEGY TO IMPROVE THE STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT FOR THE FIRST GRADE STUDENTS OF SMAN 1 BENGKULU TENGAH IN THE 2016/2017 ACADEMIC YEAR - Yudha Septian Kurniawan; BAMBANG SUWARNO; Arono Arono (JOALL (Journal of Applied Linguistics and Literature), 2017)
This research aimed to improve students’ ability in writing descriptive text by using teacher’s indirect feedback strategy for the first grade of SMAN1 Bengkulu Tengah in the 2016/2017 academic year. The subjects consisted of 30 students of Science Program. The research was conducted in two cycles, namely, each cycle consisted of planning, action, observation and reflection. Before the first cycle, the researcher gave pre-assessment. The result showed that the students’ mean score was 44,00 in absolute range, or 60,00 in relative range (poor category). After implementing cycle one, the students’ mean score in writing skill showed a little progress, especially in content’s aspect. On other hand some students were still lacking in vocabulary and language use aspects. In the second cycle, the teacher and the researcher focused to gave the students materials of two aspects above. The result was that improved to the students’ mean score : 60,76 in absolute range or 83,00 in relative range (very good category). The students’ responses were possitive toward this strategy. It was concluded that teacher’s indirect feedback strategy could improve students’ ability in writing descriptive text and it could be developed to other students.